Technological capability and R&D strengthening : a pharmaceutical industrial challenge in Indonesian - Sampurno . (Indonesian Journal of Pharmacy, 2007)
Technology and R&D capabilities are essential determinants of pharmaceutical competition in the global market. For the last thirty years, pharmaceutical industry has been dramatically changed as the impact of more significant roles of biotechnology in this industry. Pharmaceutical firms with strong capabilities in technology and R&D become market leaders and get better opportunities to sustain their competitive advantages. Indonesian pharmaceutical industry can not avoid of being involved from the trend of both regional and global competition. The harmonization of ASEAN pharmaceutical regulation in 2008 will create a single ASEAN pharmaceutical market with more complicated and wider dynamic implication, resulted in the formation of significantly competitive landscape of pharmaceutical market in the ASEAN region.Key words: Technology capabilities, R&D, Indonesian Pharmaceutical Industry